An improved virtual edge approach to slicing of point cloud for additive manufacturing. Issue 3 (4th May 2018) - Xu, Jinting; Hou, Wenbin; Zhang, Hongzhe
ABSTRACT: At present, the dense and accurate point cloud has been able to be easily acquired via various 3D measurement devices. In this situation, additive manufacturing (AM) based directly on the point cloud has been paid more attention than before. For direct slicing of the point cloud, an improved virtual edge (VE) approach is proposed. In the method, the process of constructing VEs is first discussed briefly, and then a simple algorithm of sorting contour points is given to process the scattered intersections of the VEs and the slicing plane. Subsequently, the additional points are inserted between the sparse contour points and then the contour points are adjusted onto the underlying nominal surface, thereby forming the final layered contours. Since the proposed method does not involve any nonlinear optimization, it is mathematically robust and has the ability of recognizing and processing correctly the multi-contours on a slicing plane. Finally, several examples are given to validate this method. GRAPHICAL ABSTRACT: